I think we need…: Verbal expressions of opinion in conference presentations in English and in French - Hartwell, Laura; Esperança-Rodier, Emmanuelle; Tutin, Agnès (CHIMERA: Revista de Corpus de Lenguas Romances y Estudios Lingüísticos, 2017)
This paper examines the frequency and functions of English and French opinion markers in 60 presentation transcripts of the EIIDA corpus in Linguistics and in Chemistry, Geochemistry, Marine, and Water Sciences. These functions, found in all four sub-corpora, include highlighting a general or strong opinion, proposing a hypothesis or negotiating with the audience, expressing doubt, or classifying information. Several important differences can be observed. First, the English verb think frequently functions as a discourse marker, more so than the French penser. In French, adverbials, the pronoun on and the conjunction que are frequent with an opinion verb, but were largely absent in English. In Linguistics, English speakers are more likely to express the subjective opinion that a result is “interesting”, whereas in the other three sub-corpora speakers are more likely to employ a modal verb, except with think, to hedge a statement. As regards to discipline, there appears to be slightly more markers of opinion in Linguistics. In the Sciences, markers of opinion are often related to an observation (on se rend compte, ‘one realizes’). Overall, opinion verbs tend here to be dialogic, serving to express doubt or to negotiate with the audience, rather than to confirm a forceful personal position. Keywords: oral academic discourse, opinion, English, French